RANCANGAN SISTEM PENJAMINAN MUTU DENGAN PENGENDALIAN INTERNAL BERBASIS COSO (Studi Kasus Prodi Manajemen Pendidikan Islam STAI Al Husain) - Fuad Yanuar AR (STAI Syubbanul Wathon Magelang, 2019)
COSO-based internal control can be integrated if all units have implemented it, but until now all STAIAH units have not implemented and do not have such a control system so the problem raised in this study is how to design an internal control system based on COSO. by using primary data. The analytical method used is descriptive, where the researcher will explain all the components of COSO which consist of the control environment, risk assessment, control activities, information and communication, and monitoring that are adjusted to the characteristics of the discussion within the scope of auditing and Management Control Systems. The results of this study are the COSO-based internal control system design for the Islamic Education Management study program where each component of COSO presents a set of controls that must be the attention of the leadership to be relevant to the vision and mission set by the study program. With the implementation of COSO, STAIAH especially in the Islamic Education Management study program can easily carry out control, so that it can implement the tridharma of higher education in accordance with what is stipulated by the government.